THE IMPACT OF TRANSITION ON SITUATION IN SERBIAN ECONOMY - Popov, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Serbia wants to become a member of the European union. To become a full member of the Union, Serbia must significantly improve the poor state of its economy. The paper deals with some flaw that were made ​​in Serbia in the last decade, and that seriously slowing its ability for essential integration into the Union. The analysis is focused on four issues. First, analysis indicates that the Law on Privatization is poorly structured and even poorer implemented. The result is that the privatization process is not yet finished, and in the meantime, more than a third of privatization was canceled. In the second part is concentrated on to the bad consequences of the implementation of the Law on Privatization when it comes to the ownership of land. The wrong privatization in Serbia created respective individual possessions with 15-20000 of acres. This is completely contrary to the situation in the European Union with the domination of developed cooperative movement and family farms. The third part of the paper points out the problem of illicit capital outflow from Serbia. In relation to the national income unfortunately Serbia is in these field one of the leaders. Therefore are necessary emergency measures to prevent illicit outflow. When it comes to legislative activity it is noted that more important the quality than the number of enacted laws. Future legislative activity should take into account the specificities of Serbia. Also, in order to achieve better economic results advantage should be given to the development policy, which is oriented toward the needs of Serbia.